2006
DOI: 10.1116/1.2180257
|View full text |Cite
|
Sign up to set email alerts
|

Raman study of multiwalled carbon nanotubes functionalized with oxygen groups

Abstract: We present changes in the first and second order Raman spectra of multiwalled carbon nanotubes ͑MWNTs͒ functionalized with oxygenated groups. The oxygen groups were introduced onto the nanotube surface through two strong acid purification routes: ͑1͒ reflux in concentrated ͑70%͒ HNO 3 acid for 4 h at 80°C and ͑2͒ ultrasonification in 3 HNO 3 ͑70% ͒ :1H 2 SO 4 ͑98%͒ for 8.5 h. Raman spectroscopy, using two laser excitation wavelengths ͑514.5 and 632.8 nm͒, x-ray photoelectron spectroscopy, and thermal gravimetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
138
1
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(155 citation statements)
references
References 25 publications
13
138
1
3
Order By: Relevance
“…7,8,24,34 Figure 3 presents the curves corresponding to the mass loss as a function of temperature (Figure 3a) and the derivative of the TGA curve (DTG) (Figure 3b). The thermogram in Figure 3a shows only one stage of decomposition for the MWCNT sample at temperatures between 450 and 650 ºC, which is a typical result for a MWCNT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8,24,34 Figure 3 presents the curves corresponding to the mass loss as a function of temperature (Figure 3a) and the derivative of the TGA curve (DTG) (Figure 3b). The thermogram in Figure 3a shows only one stage of decomposition for the MWCNT sample at temperatures between 450 and 650 ºC, which is a typical result for a MWCNT.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of acid treatment on the structure and morphology of the tubes have been described in depth in previous studies. [7][8][9][10][11][12] Methods based on carboxylation present advantages in that CNT can be Vol. 23, No.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the intensity ratio I D /I G 0 is suggested to be a sensitive measure for the defect concentration in carbon nanotubes by some authors. 57,58 An assignment of additional modes visible in the Raman spectra of SWCNTs can be found in the review articles by Saito et al 59 and Dresselhaus et al…”
Section: 21mentioning
confidence: 99%
“…The maximum intensity of the G and (Figure 3a). This shift may have been caused by the heavy functionalisation and electron transfer to the nanotube bundle to form NO À 3 anions [31,34]; the interstitial volume in SWCNT bundles is usually easily accessed to form such a charge-transfer compound, while MWCNTs or CNFs do not tend to form such tube bundles [35]. For the other CNSs the changes are within the standard deviation.…”
Section: Resultsmentioning
confidence: 62%
“…The I G /I D ratios were determined by analysing the band heights (instead of their areas), since the Raman spectra of some CNSs do not show well resolved G and D bands to allow band area measurements or unique deconvolutions by fitting, for example with Lorentzian line shapes. It is important to point out that it has been shown that use of intensity or area ratios in this kind of analysis yields similar results [31].…”
Section: Resultsmentioning
confidence: 96%